2019
DOI: 10.1177/0022185618817069
|View full text |Cite
|
Sign up to set email alerts
|

“Is your gig any good?” Analysing job quality in the Australian platform-based food-delivery sector

Abstract: This qualitative industry case study evaluates job quality in the Australian platform-based food-delivery sector, one part of the growing gig economy where workers, as independent contractors, engage in digitally-enabled and controlled work that is remunerated on a piece rate basis. Using a multi-dimensional framework, we draw on worker accounts of economic security, autonomy and enjoyment to assess job quality. This study posits that to achieve a more refined picture of job quality, both objective and workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
202
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(238 citation statements)
references
References 37 publications
(47 reference statements)
2
202
0
10
Order By: Relevance
“…A recent Australian study, also sponsored by Uber and focusing on its drivers, found that 78 per cent of these workers had ‘joined Uber for the flexibility [it provides] to balance their work, study and family commitments’ (AlphaBeta, : 3). Workers engaged by other leading platforms, such as Deliveroo, also see their work as having a high degree of temporal flexibility (Goods et al , ). Armed with evidence of this kind, it is relatively easy to depict gig work as harmless and to imply that it should be of little concern to regulators (Healy et al , ).…”
Section: Platforms’ Labour Practices and Their Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Australian study, also sponsored by Uber and focusing on its drivers, found that 78 per cent of these workers had ‘joined Uber for the flexibility [it provides] to balance their work, study and family commitments’ (AlphaBeta, : 3). Workers engaged by other leading platforms, such as Deliveroo, also see their work as having a high degree of temporal flexibility (Goods et al , ). Armed with evidence of this kind, it is relatively easy to depict gig work as harmless and to imply that it should be of little concern to regulators (Healy et al , ).…”
Section: Platforms’ Labour Practices and Their Consequencesmentioning
confidence: 99%
“…In contrast to a prevailing company rhetoric of choice and entrepreneurship (Roberts and Zietsma, ; Ravenelle, ), gig work is seen as insecure and exploitative by many labour and organisational scholars (Stanford, ; Van Doorn, ; Aroles et al , ). Flexibility for workers is constrained, in practice, by performance surveillance and intense competition for the best‐paid tasks (Scheiber, ; Lehdonvirta, ; Goods et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Только после того, когда заказ окажется у курьера в руках, приложение сообщит ему маршрут до места назначения. Причем все эти действия необходимо совершить в рамках тайминга, рассчитанного алгоритмом [Goods et al 2019;Shapiro 2018]. В рамках маркетплейсов деятельность работников не регламентируется столь жестким образом, хотя элементы алгоритмического управления, несомненно, присутствуют.…”
Section: когда твой босс -алгоритмunclassified
“…От фабрики к платформе: автономия и контроль в цифровой экономике довой автономии, алгоритмическое управление не только лишает работников возможностей принятия решений, но, по сути, делает неизвестными правила игры, затрудняя стратегические действия. Эмпирические исследования изобилуют примерами парадоксов и разочарований, с которыми сталкиваются работники такси или курьеры служб доставки, когда пытаются хотя бы в общих чертах разгадать принципы действия алгоритмов, чтобы получить преимущества в конкуренции за заказы или переиграть систему [Goods et al 2019;Rosenblat, Stark 2016]. Дело не только в том, что сами алгоритмы чрезвычайно изощрены, но и в том, что они постоянно видоизменяются, в том числе в результате самообучения.…”
Section: когда твой босс -алгоритмunclassified
See 1 more Smart Citation